Linguistic features of English and Vietnamese newspaper headlines in Voa news / Le Thi Mai Thu; Supervisor: Dr. Dang Ngoc Huong - Le, Thi Mai Thu
The thesis aims at unravelling salient linguistic features of a non-native variety of English as used in a different text type - that is headline. From this point, the thesis addresses the headlines of English and Vietnamese news lexically and syntactically from a contrastive perspective. To meet the above aims, this study attempts to compare and contrast news headlines in English and Vietnamese language published in an American news site to figure out the types, the roles of lexical and syntactic features of newspaper headlines. The second, some differences and similarities between newspaper headlines of the two languages will be discovered. The last portion of the study is intended to analyze the implications of the findings to language teaching and translating. The thesis is also hoped to present further insights on how headlines are constructed and provide basis for more studies on the genre. In order to accomplish the aims of the research, the qualitative approach will be first used. The following is quantitative approach. The last one is a combination of qualitative and quantitative approaches. The study employs three main methods namely data collecting and material analysis research method, descriptive research method, and contrastive method. The findings from the study hopefully will benefit not only translators of the two languages but also teachers and researchers who are interested in the issue. Criticism and comments are welcome for more profession of the thesis.